РАЗВИТИЕ ПРИНЦИПОВ ПОСТРОЕНИЯ ВЫСОКОВОЛЬТНЫХ ЦИФРО-АНАЛОГОВЫХ ПРЕОБРАЗОВАТЕЛЕЙ - Таранов , С.Г.; Тесик , Ю.Ф.; Карасинский , О.Л.; Мороз , Р.Н. (Інститут електродинаміки НАН України, Київ, 2014)
The work of the generator for reproduce a wide range of parameters of the voltages network is considered. A new principle of switching reference voltages of high-voltage DAC is proposed. The principle of action of the device, the structural scheme, formulas and graphs depicting the processes in the respective circuits are given. References 4, figures 4.